PENGAMANAN DATA NASABAH DENGAN METODE ENKRIPSI RC4 & STEGANOGRAFI LSB - Kurniawan, Arif; Husni Al Amin, Imam (Information Technology and Telematics, 2018)
Abstract Cooperative information system is one website that has a process of saving and borrowing as well as storage of process proceeds to the database and storage of customer data. This customer data is very important for customer's question to the cooperative, then this customer data must be secured. Security in a data is very important in the deployment of the system online. There are many possible data that can be taken or misused by others. This study aims to perform security on customer data to be safely maintained. This research uses method of RC4 Encryption and LSB Steganography. The result of this research is Saving and Loan Cooperative Information System with process storage and customer data that apply RC4 encryption and LSB Steganography on customer data security.